DL-Tryptophan Alleviates Sepsis-Related Acute Liver Injury via AhR Activation - Li B; Wang Q; Hu L; Duan W; Chen Y; Wang Z; Liu C; Liao L (Journal of Inflammation Research)
Baitian Li,1,* Qing Wang,2,3,* Lungui Hu,3 Wenying Duan,3 Yuxuan Chen,3 Zetian Wang,3 Chunzheng Liu,3 Lijun Liao3 1Department of Emergency Medicine, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230601, People’s Republic of China; 2Shanghai YangZhi Rehabilitation Hospital, Shanghai, 201619, People’s Republic of China; 3Department of Pain Management, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, 200433, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lijun Liao, Department of Pain Management, Shanghai East Hospital, School of Medicine, Tongji University, Shanghai, 200120, People’s Republic of China, Email liao@pan-support.com Chunzheng Liu, Department of Pain Management, Shanghai East Hospital, School of Medicine, Tongji University, Shanghai, 200120, People’s Republic of China, Email lcz980712@163.comIntroduction: This research sought to elucidate the extent to which DL-tryptophan may confer protection against sepsis-induced acute liver damage (SALI) and to investigate the underlying mechanisms, particularly emphasizing aryl hydrocarbon receptor (AhR) activation.Methods: Cecal ligation and puncture (CLP) was utilized to create a murine sepsis model. Liver inflammatory factor levels were quantified via real-time PCR, and liver damage was measured by measuring AST and ALT levels. H&E staining was utilized to evaluate histological alterations, whereas macrophage responses were examined using F4/80+ labeling. TUNEL labeling was utilized to assess hepatocyte apoptosis. The interactions between DL-tryptophan and AhR were analyzed via molecular docking. Western blotting was utilized to verify AhR expression, and its function was subsequently investigated using the AhR inhibitor CH223191.Results: DL-tryptophan markedly reduced the expression of pro-inflammatory cytokines (IL-6, TNF-α, IL-1β) and liver damage markers (AST, ALT) in CLP-induced sepsis. Histological study indicated that DL-tryptophan administration mitigated the deterioration of liver lobular architecture, edema, and inflammatory cell infiltration. Moreover, DL-tryptophan decreased macrophage infiltration and hepatocyte apoptosis. Molecular docking experiments revealed multiple interactions via which DL-tryptophan associates with AhR. The activation of AhR induced by DL-tryptophan was validated by an elevation in AhR expression, which was then reversed by CH223191, resulting in the reinstatement of pro-inflammatory cytokine production and liver damage.Discussion: DL-tryptophan may confer protection against SALI by activating AhR, thereby modulating the inflammatory response and mitigating liver damage. These findings emphasize DL-tryptophan as a prospective therapeutic agent for managing SALI and illustrate the critical role of AhR in organ preservation during septicemic circumstances. Further study is essential to elucidate the signaling pathways downstream of this action and to assess the clinical efficacy of DL-tryptophan.Keywords: sepsis-related acute liver injury, SALI, CLP, DL-tryptophan, aryl hydrocarbon receptor, AhR